The law of treaties beyond the Vienna Convention - Cannizzaro, Enzo.; Arsanjani, Mahnoush H. (Oxford : Oxford University Press, 2011)
This title offers a comprehensive analysis of the law of treaties based on the interplay between the 1969 Vienna Convention on the Law of Treaties and customary international law. Written by a team of international lawyers, it offers new insight into the basic concepts and methodology of the law of treaties and its problems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Vienna Convention on the Law of Treaties, -- (1969); Treaties